Accountability of Armenia for war crimes committed during and after the First Karabakh War: Challenges and Perspectives - Huseynova, Durdana; Shiraliyev, Ahmad; Nabiyeva, Mehri; Gorchubayli, Fayyaz (ADA University, 2024)
Genocide represents one of the gravest crimes against humanity and ensuring that those responsible are held accountable is so important that it sends a powerful message that such atrocities will not be tolerated. According to the studies it is found that there are voids in the promotion of the evidence, lack of documentation and their preservation. This capstone project emphasizes on the gaps within promotion of evidence for holding Armenia accountable for war crimes committed during and after the First Karabakh War. The aim of the paper is to conduct an investigation into the gaps and obstacles that hinder the promotion of evidence. Based on the quantitative research methods, by analyzing articles and interviewing professionals, we tried to uncover underlying issues such as inadequate resources, institutional barriers, methodological limitations, and systemic biases that hinder the promotion of evidence-based practices, policies, and decision-making processes. We ended up emphasizing three main obstacles and problems in the promotion of evidence: 1) Armenian Diaspora and Biased Action; 2) Lack of the necessary Documentation and Preservation of evidence; 3) Political Impediments to Accountability not clear. Furthermore, this paper suggests various policy options and gives each of their evaluations according to five criteria: equity, feasibility, effectiveness, efficiency, and adaptability. Moreover, this paper also provides analysis and critiques of findings during the research and emphasize the importance of enlightenment of evidence in the international community as well.
Keywords: War crimes -- Accountability -- Armenia; Genocide -- Prevention -- Armenia; International criminal law -- War crimes; Armenian diaspora -- Political influence; Public and International Affairs